Pré-tratamento de fibras de bagaço de cana-de-açúcar e seu uso em altos teores em compósitos com polipropileno via mistura termocinética - Lazarini, Rafael Gouveia (2020)
Agroindustrial residue from sugarcane generate more than 200 million tons of bagasse annually, rich in plant fibers that can be potentially applied in polymer composites. New processing routes are required to process composites with fiber contents above 50% w/w. The objective of this work was to pre-treat in natura bagasse fibers and incorporate them to polypropylene (PP) at high contents in the development of composites via thermokinetic mixture. The fibers were subjected to different chemical pre-treatments, which improved their thermal stability and increased crystallinity. Pre-treatments with 0.25 mol.L-1 of H2SO4 and NaOH were carried out on a large scale. Three grades of PP were investigated for their processability and degradation, with H201 being chosen for the composite formulation. These varied in fiber content between 50 and 80% w/w, and for the extremes, the effects of fibers pre-treatment and the use of SEBS-g-MA were evaluated. In general, composites with 50 and 60% showed a traditional composites morphology (matrix-interface-fiber), while those with 70 and 80% resembled agglomerated composites. The water absorption varied between 5 and 34%, increasing with fiber content. The crystallinity of the polymeric phase reached up to 55%. The flexural strength and the flexural modulus reached 31 MPa and 2.4 GPa, respectively, tending to decrease with fiber content. The impact strength of the composites reached 41 J.m-1. The pre-treatment of the fibers was effective only in composites with a lower fiber content, improving flexural strength. SEBS-g-MA acted as a compatibilizer in composites with 50 and 60% fibers, while it served as an impact modifier in the other ones. In summary, the work showed the viability of the processing route and good final properties of the materials, comparable to those used in similar applications, like MDF, WPC and particleboards.